Genetic or Other Causation Should Not Change the Clinical Diagnosis of Cerebral Palsy. (July 2019) - MacLennan, Alastair H.; Lewis, Sara; Moreno-De-Luca, Andres; Fahey, Michael; Leventer, Richard J.; McIntyre, Sarah; Ben-Pazi, Hilla; Corbett, Mark; Wang, Xiaoyang; Baynam, Gareth; Fehlings, Darcy; Kurian, Manju A.; et al.
High throughput sequencing is discovering many likely causative genetic variants in individuals with cerebral palsy. Some investigators have suggested that this changes the clinical diagnosis of cerebral palsy and that these individuals should be removed from this diagnostic category. Cerebral palsy is a neurodevelopmental disorder diagnosed on clinical signs, not etiology. All nonprogressive permanent disorders of movement and posture attributed to disturbances that occurred in the developing fetal and infant brain can be described as "cerebral palsy." This definition of cerebral palsy should not be changed, whatever the cause. Reasons include stability, utility and accuracy of cerebral palsy registers, direct access to services, financial and social support specifically offered to families with cerebral palsy, and community understanding of the clinical diagnosis. Other neurodevelopmental disorders, for example, epilepsy, have not changed the diagnosis when genomic causes are found. The clinical diagnosis of cerebral palsy should remain, should prompt appropriate genetic studies and can subsequently be subclassified by etiology.